Total Hip Replacement: Exchange of a Loose Perforated Press-Fit Cup with a Porous-Coated Press-Fit Cup in a Dog - Colthurst, Stephanie M.M.; Simcock, James O.; Cashmore, Ricky G. (VCOT Open, 2020)
Objective The aim of this study was to report the successful revision of a loose perforated press-fit cup by exchange with a porous-coated press-fit cup while maintaining the original locking stem and head–neck unit.Methods Cup revision was performed in a dog with a loose acetabular cup that had undergone total hip replacement with a perforated press-fit cup and locking stem 29 months previously. The original locking stem was well integrated. A single session cup exchange was performed by implantation of a 28-mm porous-coated press-fit cup with 16 mm internal diameter to allow the original locking stem and head–neck unit to be preserved.Results Revision total hip arthroplasty by cup exchange resulted in excellent functional outcome with long-term follow-up 18 months postoperatively. There were no intraoperative or postoperative complications.Conclusion A loose perforated press-fit cup was successfully revised with a porous press-fit cup while allowing preservation of the initial locking stem and head–neck unit.
Keywords: dog; revision surgery; cup exchange; cementless; total hip replacement